1999
DOI: 10.1046/j.1365-2362.1999.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum hyaluronan as a predictor of hepatic regeneration after hepatectomy in humans

Abstract: It has been suggested that hepatic regeneration is closely related to both hepatic fibrosis and hepatic sinusoidal capillarization. The serum hyaluronan level is regarded as a useful predictor for hepatic regeneration after hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…29 A high preoperative serum HA concentration was associated with impaired hepatic regeneration after hepatectomy. 11 We previously found that serum HA levels were inversely correlated with the regeneration rate of the remnant liver 9 and the present study showed the same tendency, although without significance. Because the regeneration of the injured liver is impaired, measuring the serum HA level before hepatectomy could help to predict the postoperative growth capacity of the diseased liver.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…29 A high preoperative serum HA concentration was associated with impaired hepatic regeneration after hepatectomy. 11 We previously found that serum HA levels were inversely correlated with the regeneration rate of the remnant liver 9 and the present study showed the same tendency, although without significance. Because the regeneration of the injured liver is impaired, measuring the serum HA level before hepatectomy could help to predict the postoperative growth capacity of the diseased liver.…”
Section: Discussionsupporting
confidence: 74%
“…The findings of our preliminary study and those of others showed that serum HA concentrations were inversely correlated with measurements of functional liver reserve and the degree of hepatic fibrosis, suggesting that measuring the HA level might be useful for monitoring liver damage or predicting postoperative complications after hepatic resection. [4][5][6][9][10][11] We also found that the serum HA level in patients with normal liver function was significantly lower than that in patients with liver injury caused by chronic hepatitis, cirrhosis, or obstructive jaundice, and that there were few posthepatectomy complications in patients with prehepatectomy normal liver function. 9 Thus, we conducted this study on patients with injured liver diseases to determine the efficiency of measuring the serum HA level before and after hepatectomy.…”
Section: Introductionmentioning
confidence: 51%
“…The serum HA level correlated with hepatic ATP levels and mortality rate after extensive hepatectomy in rats [42]. Ogata et al reported that preoperative serum HA concentrations > 200 ng/ml were associated with the inhibition of hepatic regeneration after hepatectomy [16]. Because major hepatectomy itself causes an increased risk of these postoperative complications, it would be difficult to determine extent of major hepatectomy in patients with a high HA level [43].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that HA was significantly associated with poor hepatic function and postoperative complications such as longterm ascites and hepatic fibrosis [14,15]. HA might be the most important factor related to poor hepatic functional reserve [16]. Therefore, we hypothesized that the serum HA level, which is a marker of reliable hepatic function, could be applied to predict patient survival in HCC patients.…”
Section: Introductionmentioning
confidence: 96%
“…The serum HA level has been recognized not only as fibrosis or a functional marker of an injured liver [31], but also as a predictor of postoperative complications associated with liver surgery [13,14,15]. Previously, a serum HA level <160 ng/ml was reported to be the discrimination value in a major hepatectomy [15] and >200 ng/ml was reported to indicate an inhibition of liver regeneration after a hepatectomy [32]. In this study, the serum HA level was also a strong predictor for postoperative complications after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%